Pattern of Recurrence in 428 Patients With Thoracic Esophageal Squamous Cell Carcinoma After Radical Surgery and Its Implication in Postoperative Radiotherapeutic Clinical Target Volume - Cui, Tiantian; Zhang, Hongjiao; Yu, Tao; Chen, Yiru; Liu, Chengxin; Zhao, Qian; Zhu, Jian; Li, Baosheng; Huang, Wei (Frontiers in Oncology, 2021)
Abstract Purpose: The study was to investigate recurrence patterns of thoracic esophageal squamous cell carcinoma (ESCC) after radical surgery and its implication in the clinical target volume (CTV) designed of postoperative radiotherapy (PORT) in patients with ESCC. Methods and materials: A total of 428 recurrent ESCC patients after radical surgery between 2014 and 2018 were included in this study. Recurrence patterns, especially anastomotic and regional lymph node recurrence (LNR), were analyzed. A T-shaped CTV were proposed for PORT and were evaluated whether it could cover most of regional LNR. Results: These patients all experienced anastomotic and/or regional LNR. Among the 428 patients, 27 cases (6.3%) had anastomotic recurrence only, 184 cases (43.0%) had LNR only. Those sites with LNR rate higher than 15% in upper thoracic ESCC were as follows: No.101, No.104R, No.104L, No.106recR, No.106recL, No.106pre, No.106tb, No.107, No. 109; those in middle thoracic ESCC were as follows: No.104R, No.104L, 106recR, No.106recL, No.106pre, No.106tb, No.107; and those in lower thoracic ESCC were as follows: No.104L, 106recR, No.106recL, No. 106pre, No. 106tb, No.107 and abdominal No. 3. The proportion of LNR not included in the proposed T-shaped CTV was 12.5% (1/8), 4.7% (6/128) and 10.4% (5/48) in the upper, middle and lower thoracic segment respectively. Conclusions: LNR was the most common type of local-regional recurrence in patients after radical surgery. Supraclavicular, superior and middle mediastinal lymph nodes had the highest recurrence rate, the rate of LNR which was outside T-shaped PORT CTV we proposed was less than 15%.